A Simple Correlation for Assessment of the Shock Wave Energy in Underwater Detonation. Issue 18 (10th October 2019) - Keshavarz, Mohammad Hossein; Bagheri, Vahid
Abstract : Assessment of underwater detonation (explosion) is important for industrial purposes such as blasting cut of old warship, blasting droll and decoupled charge of blast underwater. Calculation of the shock wave energy requires several expensive experimental data such as the shock wave pressure and the representative time of the process. This work introduces a simple method for reliable prediction of the shock wave energy of composite explosives containing aluminum (Al) and/or ammonium perchlorate (AP), which show non‐ideal behavior. This method is based on the composition, loading density and the ratio of R/m 1/3, where R is the distance between the pressure gauge and charge as well as m is the mass of explosive charge. The measured data for 86 and 21 composite Al/AP explosives are used to construct and test the new model. Statistical parameters including the root mean squared error (RMSE), and maximum of errors (Max Error) of the new model are 0.11 and 0.39 MJ· kg –1, respectively, which confirm high reliability of the new method. The values of RMSE and Max Error for test set are 0.13 and 0.30 MJ· kg –1, respectively. Cross validation of the novel model is also used to evaluate its goodness‐of‐fit, goodness‐of‐prediction, accuracy and precision. It is shown that the novel correlation can be applied for pure and composite explosives without Al/AP. Abstract :